If you would like to solve the equation - 2/5 * x + 6 = 8, you can do this using the following steps:
- 2/5 * x + 6 = 8
- 2/5 * x = 8 - 6
- 2/5 * x = 2 /*(-5/2)
x = 2 * (- 5/2)
x = - 5
The correct result would be -5.
Answer:
21
Step-by-step explanation:
So, the negative would be divided out to make it 3, then square both sides to get rid of the square root and get 9, then subtract 15 and you get -6. <span />
If "x" is a multiplication sign:
-3 * 98 + 193 =
-294 + 193 =
101
Hope it helped,
BioTeacher101
Answer:
When we add two or more whole numbers, their sum is the same regardless of the order of the addends. The sum of both 2 + 4 and 4 + 2 is 6. That means, we can add whole numbers in any order. When three or more numbers are added, the sum is the same regardless of the grouping of the addends.
Step-by-step explanation:
there